2019
DOI: 10.1002/bit.27023
|View full text |Cite
|
Sign up to set email alerts
|

Validation and optimization of viral clearance in a downstream continuous chromatography setting

Abstract: Continuous bioprocessing holds the potential to improve product consistency, accelerate productivity, and lower cost of production. However, switching a bioprocess from traditional batch to continuous mode requires surmounting business and regulatory challenges. A key regulatory requirement for all biopharmaceuticals is virus safety, which is assured through a combination of testing and virus clearance through purification unit operations. For continuous processing, unit operations such as capture chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Previous studies on the viral clearance capability of continuous chromatography have shown that alternate modes of capture do not affect this capability of viral removal. 56,57 The AEX step in these processes remains unchanged in how load material is applied (i.e., directly from an intermediate pool, and not directly from a prior column eluate), and so its viral removal capability would not differ for this robust viral clearance step. Therefore, quality attributes can be reliably controlled for intensified fed-batch manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the viral clearance capability of continuous chromatography have shown that alternate modes of capture do not affect this capability of viral removal. 56,57 The AEX step in these processes remains unchanged in how load material is applied (i.e., directly from an intermediate pool, and not directly from a prior column eluate), and so its viral removal capability would not differ for this robust viral clearance step. Therefore, quality attributes can be reliably controlled for intensified fed-batch manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of manufacturing therapeutics using CHO cells, viral clearance is mandatory (Chiang et al, 2019;Jungbauer, 2019). Viral clearance for mAbs production processes uses a low pH hold because the protein elution occurs at low pH from a Protein A chromatography column.…”
Section: Continuous Viral Inactivation and Clearancementioning
confidence: 99%
“…Four to five steps are evaluated for viral reduction, including protein A and other column chromatography steps where the mAb is bound and other components flow through (see Box 2 for difficulties in viral detection).
Rapid Viral Detection: A Difficult Challenge Current methods for detecting viruses are based on PCR assays, animal infection susceptibility, immune responses, or cell culture infectivity assays [ 36 , 69 ]. Methods, such as reverse transcription loop-mediated isothermal amplification [ 70 ] and next-generation sequencing, hold the potential to decrease the amount of time required for detecting viruses while maintaining the same limits of detection as traditional methods (one viral copy per cell).
…”
Section: Downstream Processingmentioning
confidence: 99%
“…Current methods for detecting viruses are based on PCR assays, animal infection susceptibility, immune responses, or cell culture infectivity assays [ 36 , 69 ]. Methods, such as reverse transcription loop-mediated isothermal amplification [ 70 ] and next-generation sequencing, hold the potential to decrease the amount of time required for detecting viruses while maintaining the same limits of detection as traditional methods (one viral copy per cell).…”
Section: Downstream Processingmentioning
confidence: 99%